The Implementation of Short English Movie to Improve Students’ Vocabulary Mastery in Interpretive Listening Class - Densiana Tnomat; Marthisa Oliva Billik; Tri Buce. J Banu (SAGA: Journal of English Language Teaching and Applied Linguistics, 2022)
This paper aims to investigate the students’ vocabulary mastery improvement after the implementation of a short English movie in Interpretive Listening class. There were 15 students of Interpretive Listening class of STKIP SoE as the participants. The researcher used Classroom Action Research as the method and collected the data by using test, in the form of pretest, posttest and observation for the students’ vocabulary mastery. The result of the study indicated that short English Movie can improve students’ vocabulary mastery. The improvement covered, the students’ being active in the process of teaching and learning in the classroom.